Phytase with Synergistic Herbs: An Option to Reduce Environmental Pollution by Partial Replacement of Inorganic Phosphorus in Broiler Ration - Somkuwar, A.P.; Ravikanth, K.; Maini, S.; Rekhe, D.S.; Patil, M.K.; Ballurkar, B. (International Journal of Poultry Science, 2010)
Supplementation of phytase alongwith certain synergistic herbs (Ayufytase) was assessed on growth performance, phosphorus excretion and bone mineralization in 6 weeks trial using 90 day old Vencob broiler chicks fed corn-soyabean based diet. Chicks were randomly divided into three equal groups (n = 30), each having three replicates. Composition of experimental diets for all three groups were designed in a way that group T0 was offered standard basal diet formulated as per NRC (1994) requirements containing Dicalcium Phosphate (DCP) as the source of inorganic phosphorus and without any phytase supplementation, T1 was offered basal diet with supplemental Ayufytase@100gm/tonne of feed replacing 50% of DCP, T2 was offered basal diet with Ayufytase@100gm/tonne of feed replacing 65% of DCP. Feed intake and body weight gain was recorded on weekly basis. A metabolic trial of three days was conducted at the end of the trial to estimate percent (%) Phosphorus (P) excreted in faeces. Among bone mineralization parameters; tibia ash, toe ash, phosphorus %, tibiotarsal and robusticity index were determined at 6th week. The results of treatment group (T1 and T2) reveals significant (p